Sustainable barrier paper coating based on alpha-1, 3 glucan and natural rubber latex. (15th April 2022) - Adibi, Azin; Valdesueiro, David; Mok, Jorge; Behabtu, Natnael; Lenges, Christian; Simon, Leonardo; Mekonnen, Tizazu H.
Abstract: There is an increasing interest in utilizing more sustainable and inherently biodegradable materials alternatives ideally derived from renewable resources for modern material applications, especially in the area of packaging materials. This work employed the polysaccharide alpha-1, 3-glucan derived from an enzymatic polymerization process as a functional additive for natural rubber (NR) latex-based coating films. Coating formulations containing NR and 9–50 wt% alpha-1, 3 glucan were prepared and then applied to paper substrates at different thicknesses. The effect of coating formulations on the barrier properties (e.g., oxygen, oil, water vapor barrier), the viscosity, and dry and wet tensile properties were investigated. The NR/glucan coatings exhibited outstanding tensile properties and balanced oxygen and oil barrier performance. However, higher glucan loading could be detrimental to moisture barrier. Overall, this study indicated that the NR/glucan coating films are comparable in performance to commercial coating formulations while providing a renewable, potential to be recycled with paper, and biodegradable alternative. Graphical abstract: Unlabelled Image